Fibroblast growth factor receptor‐1 as a potential therapeutic target in sinonasal cancer. Issue 9 (1st February 2014) - Schröck, Andreas; Göke, Friederike; Wagner, Patrick; Bode, Maike; Franzen, Alina; Huss, Sebastian; Agaimy, Abbas; Ihrler, Stephan; Kirsten, Robert; Kristiansen, Glen; Bootz, Friedrich; Lengerke, Claudia; et al.
Abstract Background Despite multimodal treatment, sinonasal malignancies have an unfavorable prognosis. The purpose of this study was to elucidate if these tumors harbor amplifications of the fibroblast growth factor receptor 1 (FGFR1) gene, which has recently been identified as a potential therapeutic target in squamous cell lung cancer. Methods One hundred twelve primary tumors (including squamous cell carcinoma [SCC], carcinoma associated with an inverted papilloma, sinonasal undifferentiated carcinoma [SNUC], adenocarcinoma, adenoid cystic carcinoma [ACC], esthesioneuroblastoma, and 9 corresponding lymph node metastases) were assessed by fluorescence in situ hybridization (FISH) for FGFR1 copy number status. Human papillomavirus (HPV) status was assessed by p16 immunohistochemical as a surrogate marker. Results FGFR1 amplification was found in subsets of sinonasal SCCs (20%), carcinomas associated with an inverted papilloma (33%), and SNUCs (5%). In all cases, metastatic tumor samples shared the same FGFR1 amplification status as the corresponding primary tumor tissue. None of the FGFR1‐amplified tumors expressed p16. Conclusion FGFR1 amplification represents a potential molecular target in a subset of patients with sinonasal cancer. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1253–1257, 2014